The Guaymas Basin Hiking Guide to Hydrothermal Mounds, Chimneys, and Microbial Mats: Complex Seafloor Expressions of Subsurface Hydrothermal Circulation - Teske, Andreas; de Beer, Dirk; McKay, Luke J.; Tivey, Margaret K.; Biddle, Jennifer F.; Hoer, Daniel; Lloyd, Karen G.; Lever, Mark A.; Røy, Hans; Albert, Daniel B.; Mendlovitz, Howard P.; MacGregor, Barbara J. (Frontiers in Microbiology, 2016)
The hydrothermal mats, mounds, and chimneys of the southern Guaymas Basin are the surface expression of complex subsurface hydrothermal circulation patterns. In this overview, we document the most frequently visited features of this hydrothermal area with photographs, temperature measurements, and selected geochemical data; many of these distinct habitats await characterization of their microbial communities and activities. Microprofiler deployments on microbial mats and hydrothermal sediments show their steep geochemical and thermal gradients at millimeter-scale vertical resolution. Mapping these hydrothermal features and sampling locations within the southern Guaymas Basin suggest linkages to underlying shallow sills and heat flow gradients. Recognizing the inherent spatial limitations of much current Guaymas Basin sampling calls for comprehensive surveys of the wider spreading region.